Mycorrhiza re-establishment on post-mined rehabilitated areas of the Brand se Baai Succulent Karoo vegetation. - Ndeinoma, Albertina (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Botany and Zoology)--University of Stellenbosch, 2006.